EBV-positive diffuse large B cell lymphoma secondary to activated phosphoinositide 3 kinase δ syndrome type 1 (APDS1): a case report and literature review - Xiang, Qiu-yuan; Zuo, Min; Zhou, Ji-Hao; Feng, Chun (Frontiers in Immunology, 2025)
Activated phosphoinositide 3-kinase δ syndrome (APDS), an inborn error of immunity associated with gain-of-function mutations in the PIK3CD gene, is characterized by dysregulated PI3Kδ signaling. The clinical spectrum commonly includes recurrent respiratory infections and lymphoproliferative manifestations. We present an adolescent male with APDS1 manifesting recurrent sinopulmonary infections, generalized lymphadenopathy, hepatosplenomegaly, gastrointestinal manifestations, and combined T-cell/B-cell lymphopenia, complicated by Epstein-Barr virus-positive diffuse large B-cell lymphoma (EBV+ DLBCL). Whole-exome sequencing identified a heterozygous PIK3CD variant (c.3061G>A p.Glu1021Lys), supporting the molecular diagnosis of APDS1. This case adds to emerging evidence linking APDS1 with EBV-driven lymphomagenesis, thereby further supporting the critical role of PI3K δ pathway dysregulation in promoting EBV-associated lymphoid malignancies.